KURIKULUM PENDIDIKAN DALAM AL-QUR’AN DENGAN PENDEKATAN TAFSIR MAUDHU’I - Sadiah Sadiah; Akhmad Alim (JURNAL TARBIYAH, 2025)
The separation of religious and general sciences hinders a holistic understanding of Islam and the intellectual and spiritual balance of students, so that students do not live religious values in their daily lives. This study aims to design a Qur'an-based curriculum with a Tafsir Maudhu'i approach and explore the practical implementation of the Qur'anic education curriculum. The approach used in this research is thematic tafsir method. The results of this study indicate that in the Qur'an and hadith there are verses that discuss various aspects of the Islamic education curriculum, including the curriculum of tawhid, morals, social education, science, worship, da'wah, tazkiyatunnafs, and ethics and manners. Implementative studies in the education curriculum in the Qur'an emphasize that the Islamic education curriculum must be based on the principle of tawhid. This principle underlines unity in various aspects, such as the integration of individual and social piety, religious and general science, faith and reason, and the integration of aqidah, sharia, and morals. The curriculum is structured in accordance with human nature. The goal is to form individuals who have faith, noble character, and provide benefits to society. In addition, the division of knowledge in the curriculum is based on the belief that all knowledge comes from Allah, complements each other, and aims to achieve happiness in this world and the hereafter in accordance with His will.